EFEITOS DO ESTADO NUTRICIONAL E DA INTERVENÇÃO NUTRICIONAL COM PEPTÍDEOS DO HIDROLISADO DE COLÁGENO SOBRE A RESPOSTA HEMODINÂMICA CARDIOVASCULAR EM PACIENTES COM DPOC GRAVE (CIPEEX, 2026)
Introduction: Patients with severe COPD present systemic repercussions, including nutritional impairment and hemodynamic alterations. Objective: To evaluate the effects of nutritional status and supplementation with hydrolyzed collagen peptides (25 g/day for 12 weeks) on hemodynamic parameters obtained by PhysioFlow®. Methods: Clinical trial with allocation into a control group (CG) and a supplemented group (SCG). Stroke volume (SV), stroke volume index (SVI), cardiac output (CO), cardiac index (CI), systolic blood pressure (SBP), systemic vascular resistance (SVR), end-diastolic volume (EDV), and early diastolic function rate, among others, were assessed. Statistical analysis was performed using GraphPad Prism, with significance set at p
Keywords: chronic obstructive pulmonary disease (copd); Respostas hemodinâmicas; collagen; Physioflow